City-county consolidation : promises made, promises kept? - Leland, Suzanne M., 1971-; Thurmaier, Kurt M., 1957- (American governance and public policy., 2010)
Suzanne M. Leland is an associate professor in the Department of Political Science at University of North Carolina at Charlotte. Kurt Thurmaier is a professor and director of the Division of Public Administration at Northern Illinois University. --Book Jacket.